2018
DOI: 10.1002/jssc.201800336
|View full text |Cite
|
Sign up to set email alerts
|

Analytical feasibility of a solvent‐assisted flavour evaporation method for aroma analyses in bread crumb

Abstract: The analysis of bread aroma is essential in order to evaluate its quality as well as to improve it. The use of different methodologies for the analysis of volatile compounds lead to varying results. In the present study, the matrix effect, extraction efficiency, limits of detection and quantification as well as the precision of a proposed solvent-assisted flavour evaporation methodology were evaluated for the first time and compared with a reference method, both differing in the distillation step. The repeatab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…Recently, SAFE recovery data for a number of compounds from a diethyl ether/dichloromethane (ratio 2:1) bread crumb extract containing a low level of fat (less than 1%) were reported (Pico et al 2018). Given this low level of fat, the recoveries were lower than would be expected when compared to the data from the present study.…”
Section: Comparison To Previous Work On Safe Yieldscontrasting
confidence: 77%
See 1 more Smart Citation
“…Recently, SAFE recovery data for a number of compounds from a diethyl ether/dichloromethane (ratio 2:1) bread crumb extract containing a low level of fat (less than 1%) were reported (Pico et al 2018). Given this low level of fat, the recoveries were lower than would be expected when compared to the data from the present study.…”
Section: Comparison To Previous Work On Safe Yieldscontrasting
confidence: 77%
“…Though the solvent extract from bread produced by Pico et al (2018) was comparable to that reported in this study in terms of fat content, the high starch content of bread may have had an impact on the recovery data. Starch has been known to form complexes with volatile compounds (Jeon et al 2003), especially acids, and this may affect solid-liquid extraction.…”
Section: Comparison To Previous Work On Safe Yieldssupporting
confidence: 57%
“…Dichloromethane (DCM) is another solvent that is frequently used in the extraction and separation of aromatic compounds from solid food matrices. 13,14…”
Section: Methodsmentioning
confidence: 99%
“…Dichloromethane (DCM) is another solvent that is frequently used in the extraction and separation of aromatic compounds from solid food matrices. 13,14 Deodorization of YP flour or starch via Soxhlet extraction (Fig. S1 †) with redistilled PE or DCM was conducted according to the AACC Approved Method 30-25.01 with minor modifications.…”
Section: Matrix Deodorizationmentioning
confidence: 99%